2005
DOI: 10.1536/ihj.46.711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thimerosal on Arrhythmia Induced by Coronary Ligation The Involvement of ATP-dependent Potassium Channels

Abstract: SUMMARYThiol-modifying agents induce the release of nitric oxide (NO) from endothelial epithelium and the release of reactive oxygen free radicals in the vascular system. Moreover, thiol groups are essential for the functioning of the ATP dependent potassium channel (K-ATP). The effects of thiol-modifying agents and their molecular mechanisms on arrhythmia have not been widely studied. In this study, we investigated the effect of the hydrophilic SH-group-oxidizing substance thimerosal on the arrhythmia induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It has been shown that ATP dependent potassium (K ATP ) channel blockage confers protection against I/Rinduced arrhythmias (23,24). Ketamine inhibits the K ATP channel activity in a concentration-dependent manner in the rat heart (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ATP dependent potassium (K ATP ) channel blockage confers protection against I/Rinduced arrhythmias (23,24). Ketamine inhibits the K ATP channel activity in a concentration-dependent manner in the rat heart (41).…”
Section: Discussionmentioning
confidence: 99%
“…Both thiopental and ketamine+xylazine (K+X) have been used in studies involving experimental cardiology (16)(17)(18)(19)(20)(21)(22)(23)(24). However, there are only a few studies addressing the influence of anesthetics on I/R-induced arrhythmias (7)(8)(9)(10), whilst there has been no comparison between these two commonly used anesthetics (thiopental and K+X) in an in vivo I/R arrhythmia model.…”
Section: Introductionmentioning
confidence: 99%
“…The blockage of the K ATP channels by drugs has been reported to be antiarrhythmic 5 and proarrhythmic. 6 K ATP channel openers have also been described as both antiarrhythmic 7 and proarrhythmic agents. 8 Studies researching the effect of the selective K ATP channel modulators are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental surgical procedures used in the study were described before by Bozdogan et al 20 Briefly, animals were anaesthetized with thiopental sodium (85 mg/kg IP in a volume of 2 mL/kg) (Abbott, İstanbul, Turkey) and tracheotomy was used for artificial respiration. The left carotid artery was cannulated with polyethylene tubing (0.58 mm × 0.96 mm; Harvard Apparatus, Boston, Massachusetts) to record the arterial blood pressure with a blood pressure transducer (SS 13 L; Biopac Systems, Goleta, California).…”
Section: Methodsmentioning
confidence: 99%
“…The left coronary artery was retightened, and the heart was first perfused through the aorta with 10 mL isotonic sodium chloride solution, followed by 2 mL 96% ethanol for the demarcation of the occluded and nonoccluded myocardium 20 . The nonperfused area that remained red colored (ischemic risk zone) was cut along the epicardially visible border zone from the well-perfused area that seemed white in color (nonischemic myocardium mass).…”
Section: Methodsmentioning
confidence: 99%